2015
DOI: 10.1128/cvi.00661-14
|View full text |Cite
|
Sign up to set email alerts
|

Shigella Outer Membrane Protein PSSP-1 Is Broadly Protective against Shigella Infection

Abstract: dIn developing countries, Shigella is a primary cause of diarrhea in infants and young children. Although antibiotic therapy is an effective treatment for shigellosis, therapeutic options are narrowing due to the emergence of antibiotic resistance. Thus, preventive vaccination could become the most efficacious approach for controlling shigellosis. We have identified several conserved protein antigens that are shared by multiple Shigella serotypes and species. Among these, one antigen induced cross-protection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…This study also demonstrated that naturally induced ASC responses to PSSP1, an antigen recently identified as cross-protec- tive in animal studies (35), were rather infrequent and generally much weaker than the corresponding ASC responses to IpaD (and, for that matter, IpaC). This observation may indicate that such mucosal antibody responses may not develop to a level conducive to immune protection or may wane too rapidly after Shigella infection to support protection against subsequent reinfection by Shigella bacteria of the same or different species and serotypes.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This study also demonstrated that naturally induced ASC responses to PSSP1, an antigen recently identified as cross-protec- tive in animal studies (35), were rather infrequent and generally much weaker than the corresponding ASC responses to IpaD (and, for that matter, IpaC). This observation may indicate that such mucosal antibody responses may not develop to a level conducive to immune protection or may wane too rapidly after Shigella infection to support protection against subsequent reinfection by Shigella bacteria of the same or different species and serotypes.…”
Section: Discussionmentioning
confidence: 75%
“…Recent preclinical studies showed that IpaD and PSSP1 antigens can induce cross-protection against experimental shigellosis caused by several species and serotypes (35,43). We thus compared gut-homing ASC responses to IpaD20/IpaD120 and PSSP1 among shigellosis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for masking of Shigella surface proteins is provided by our studies of pan Shigella surface protein-1 (PSSP-1) the C-terminal half-polypeptide of IcsP (Fukuda et al, 1995 ) that is conserved across Shigella species (Kim et al, 2015 ). We found that PSSP-1-specific antibodies did not bind IcsP on Shigella cells, which was consistent with another report that LPS Oag of gram-negative bacteria masks other surface antigens, such as IcsP ( S. flexneri ), by preventing antibody access (van der Ley et al, 1986 ; Tran et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Still, IFNγ is known to be involved in protection against Shigella infections and response to subunit polypeptide vaccines (48). Surprisingly, S. boydii str.…”
Section: Discussionmentioning
confidence: 99%